The Correlation Among Vocabulary Mastery, Utilization Of The Environment, And Writing Ability Of Elementary School Students - Ahmad Hubaisy; Gusti Yarmi; Aminudin Zuhairi (Universitas PGRI Adi Buana Surabaya, 2023)
This study has the main objective to examine the correlation between vocabulary acquisition and environmental utilization with the writing skills of elementary school students. Using a quantitative approach with a survey method and correlation technique, this study answers three key hypotheses. First, the results indicated a significant positive correlation between vocabulary mastery and descriptive essay writing skills, with a correlation value (rcount) of 0.823, which far exceeded the significance threshold (rtable) of 0.195. Secondly, the study also found a positive relationship between the utilization of the environment as a learning resource and descriptive essay writing skills, with an rcount of 0.632 which significantly exceeds the rtabel. Finally, when analyzed together, vocabulary acquisition and environmental utilization strongly influence students' writing skills, indicated by a multiple correlation coefficient of 0.834 and a coefficient of determination of 0.695. This result illustrates that about 69.5% of the variability in descriptive essay writing skills can be explained by the combination of vocabulary acquisition and utilization of the environment as a learning resource. These findings underscore the importance of considering these two factors in educational planning to improve students' writing skills at the primary school level.